Réponses

2013-12-14T17:58:44+01:00
A) 5*2x - 5*8= 10x-40
b) -7*8 -7*3y = 56-21y
c)6*-z + 6*3 = -6z+18
d) 6*1-6*2a= 6-12a
e) -b*3b+b*7=-3b² +7b
f) 5c*4c-5c*6= 20c²-30c

2013-12-14T18:01:40+01:00
A= 5(2x-8)                   B= -7 (8+3y)
   = 5*2x-8*5                  = -7*8-7*3y
   = 10x-40                     = -56-21y

C= 6 (-z+3)                  D= 6(1-2a)
  = -z*6+6*3                    = 6*1-2a*6
  = -6z+18                       = 6-12a

E=-b (3b-7)                  F=5c (4c-6)
  = -b*3b-b*-7                 = 5c*4c-6*5c
  = -3b²+7b                     =20c²-30c

Voilà :)